A study of factors that lead to the public participation in local government activities a case study: Hang Tuah Jaya Municipal Council (MPHTJ) / Siti Nurul Fatinah Ramli and Nurul Shazwani Mohd Rosjidin - Ramli, Siti Nurul Fatinah; Mohd Rosjidin, Nurul Shazwani (Faculty of Administrative Science and Policy Studies, 2013)
This study examined the factors that contribute to public participation in local government’s activity at Hang Tuah Jaya Municipal Council (MPHTJ). This research paper studies the relationship between Independent Variables (Community, Programs, Policy and Facility) and Dependent Variable (Public Participation). The purpose of this study is to identify the most significant factor that contributes to public participation in local government’s activitiy. The researchers conduct the study in the area of MPHTJs’ district at Melaka Tengah. There are four (4) objectives for this research whereby the researchers aim to identify the factor that contributes to participation of public in local government’s activity. Besides that, researchers intended to investigate whether the service provided by local government is sufficient as well as to examine the level of awareness among public towards the activity of local government. Last but not least, the researchers intended to investigate the response of public to programs conduct by local government. At the end of this paper, researchers are analyzing the result from this study which including the reliability analysis, correlation coefficient, descriptive analysis, multiple regression and normality test and lastly the researchers also have identified the limitation and recommendation for this study as well as to assist the future researcher for this study.